2015
DOI: 10.3109/03602532.2014.1003649
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid interactions during digestion, absorption, distribution and metabolism: a sequential structure–activity/property relationship-based approach in the study of bioavailability and bioactivity

Abstract: Flavonoids are a group of polyphenols that provide health-promoting benefits upon consumption. However, poor bioavailability has been a major hurdle in their use as drugs or nutraceuticals. Low bioavailability has been associated with flavonoid interactions at various stages of the digestion, absorption and distribution process, which is strongly affected by their molecular structure. In this review, we use structure-activity/property relationship to discuss various flavonoid interactions with food matrices, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
149
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(159 citation statements)
references
References 118 publications
(206 reference statements)
4
149
0
6
Order By: Relevance
“…A more gradual and sustained insulinaemic response could potentially increase satiety during intermeal intervals (4) and a lowered postprandial glycaemia is likely to protect the optimum functionality of pancreatic β cells, the vascular endothelium and hepatic lipid metabolism. However, there may be significant technical challenges for the food and drink industry in formulating products with the desired characteristics in terms of physical and chemical stability (114) , bioavailability (107) and palatability (115) . Anthocyanin contents vary among species and cultivars, and are subject to genetic, agricultural and environmental factors as well as storage and processing conditions (116)(117)(118) .…”
Section: Discussionmentioning
confidence: 99%
“…A more gradual and sustained insulinaemic response could potentially increase satiety during intermeal intervals (4) and a lowered postprandial glycaemia is likely to protect the optimum functionality of pancreatic β cells, the vascular endothelium and hepatic lipid metabolism. However, there may be significant technical challenges for the food and drink industry in formulating products with the desired characteristics in terms of physical and chemical stability (114) , bioavailability (107) and palatability (115) . Anthocyanin contents vary among species and cultivars, and are subject to genetic, agricultural and environmental factors as well as storage and processing conditions (116)(117)(118) .…”
Section: Discussionmentioning
confidence: 99%
“…Paradoxically (with the exception of 10 µg/g concentration gradient) Increased inclusion of the moringa leaf in the condiment (at 20 to 50%) led to about 50% overall decrease in the flavonoid content of the condiment. This may be as a result of enhanced covalent interaction between the flavonoids and the proximate components (proteins, carbohydrates and fats) directly associated with physico-chemical properties (Gonzales et al, 2015). Although generally known for their antioxidative property (Arueya et al, 2015), the flavonoids in this study represent a fairly low fraction (2-38%) of the total phenolic content of the condiments depending on the concentration gradient.…”
Section: Total Flavonoid Contentmentioning
confidence: 70%
“…The formation of such complexes may lead to lowering the nutritional value of proteins by changing of their solubility, thermal stability and digestibility [40,41]. Secondly, the fact of proteins complexes formation may substantially reduce the health-promoting potential of phenolic compounds by masking of their antioxidant properties [41,42]. Our previous study indicated possibility of formation of the static complex between γ-conglutin and vitexin with a binding constants (K a ) and a number of binding places (n) of 3.47 × 10 4 M −1 and 1.017, respectively [25].…”
Section: Phenolic Compounds and Their Interaction With Lupin Seed Glomentioning
confidence: 99%
“…The growing interest in the use of lupin, as a valuable component of food is limited by the occurrence of hypersensitivity to allergic proteins of its seeds [42,43]. The problem has become so significant that the Parliament of the European Union in Directive 2006/142/EC mentioned lupin among 14 major food allergens which are responsible for 90 % of food allergies [6].…”
Section: Immunoreactive Properties Of Digested Lupin Seed Globulinsmentioning
confidence: 99%